Evolution of prokaryotic colonisation of greenhouse plastics discarded into the environment - Martínez-Campos, Sergio; Pissaridou, Panayiota; Drakou, Katerina; Shammas, Christos; Andreou, Kostas; González-Pleiter, Miguel; Fernández-Piñas, Francisca; Leganes, Francisco; Rosal, Roberto; Koutinas, Michalis; Kapnisis, Konstantinos; Vasquez Christodoulou, Marlen (My University, 2022)
Current knowledge on the capacity of plastics as vectors of microorganisms and their ability to transfer microorganisms between different habitats (i.e. air, soil and river) is limited. The objective of this study was to characterise the evolution of the bacterial community adhered to environmental plastics [low-density polyethylene (LDPE)] across different environments from their point of use to their receiving environment destination in the sea. The study took place in a typical Mediterranean intermittent river basin in Larnaka, Cyprus, characterised by a large greenhouse area whose plastic debris may end up in the sea due to mismanagement. Five locations were selected to represent the environmental fate of greenhouse plastics from their use, through their abandonment in soil and subsequent transport to the river and the sea, taking samples of plastics and the surrounding environments (soil and water). The bacterial community associated with each sample was studied by 16S rRNA metabarcoding; also, the main physicochemical parameters in each environmental compartment were analysed to understand these changes. The identification and chemical changes in greenhouse plastics were tracked using Attenuated Total Reflection Fourier Transform Infra-red spectroscopy (ATR-FTIR). Scanning Electron Microscope (SEM) analysis demonstrated an evolution of the biofilm at each sampling location. β-diversity studies showed that the bacterial community adhered to plastics was significantly different from that of the surrounding environment only in samples taken from aqueous environments (freshwater and sea) (p-value p-value > 0.05). The environmental parameters (pH, salinity, total nitrogen and total phosphorus) explained the differences observed at each location to a limited extent. Furthermore, bacterial community differences among samples were lower in plastics collected from the soil than in plastics taken from rivers and seawater. Six genera (Flavobacterium, Altererythrobacter, Acinetobacter, Pleurocapsa, Georgfuchsia and Rhodococcus) were detected in the plastic, irrespective of the sampling location, confirming that greenhouse plastics can act as possible vectors of microorganisms between different environments: from their point of use, through a river system to the final coastal receiving environment. In conclusion, this study confirms the ability of greenhouse plastics to transport bacteria, including pathogens, between different environments. Future studies should evaluate these risks by performing complete sequencing metagenomics to decipher the functions of the plastisphere.
Keywords: 16S rRNA metabarcoding; Plastisphere; Plastic waste life cycle; Plastic cycle; Greenhouse plastic; Bacterial communities